2021
DOI: 10.5194/essd-13-447-2021
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of global actual evapotranspiration from 1982 to 2019

Abstract: Abstract. As a linkage among water, energy, and carbon cycles, global actual evapotranspiration (ET) plays an essential role in agriculture, water resource management, and climate change. Although it is difficult to estimate ET over a large scale and for a long time, there are several global ET datasets available with uncertainty associated with various assumptions regarding their algorithms, parameters, and inputs. In this study, we propose a long-term synthesized ET product at a kilometer spatial resolution … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 92 publications
0
60
1
Order By: Relevance
“…The comparison with latent heat flux measured at eddy flux towers suggested that the two globally available ET products, MOD16 and SSEBop, both based on MODIS satellite data, perform similarly in the Alps. In contrast to studies indicating that SSEBop is generally more reliable than MOD16 [25], MOD16 exhibited a slightly better agreement with observed data in terms of mean daily RMSE and MBD, probably because the spatial resolution plays a crucial role in heterogenous mountain regions. It is reasonable to assume that a MOD16 spatial resolution of 500 m captures the heterogeneity of Alpine vegetation better than the SSEBop spatial resolution of 1 km.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…The comparison with latent heat flux measured at eddy flux towers suggested that the two globally available ET products, MOD16 and SSEBop, both based on MODIS satellite data, perform similarly in the Alps. In contrast to studies indicating that SSEBop is generally more reliable than MOD16 [25], MOD16 exhibited a slightly better agreement with observed data in terms of mean daily RMSE and MBD, probably because the spatial resolution plays a crucial role in heterogenous mountain regions. It is reasonable to assume that a MOD16 spatial resolution of 500 m captures the heterogeneity of Alpine vegetation better than the SSEBop spatial resolution of 1 km.…”
Section: Discussioncontrasting
confidence: 93%
“…Both ET products seem to be a good compromise in terms of physical robustness of the retrieval algorithm, applicability to large areas, spatial resolution (500 m × 500 m for MOD16 and 1 km × 1 km for SSEBop), length of the timeseries (almost 20 years), and temporal resolution (8 days for MOD16 and 10 days for SSEBop). The literature shows that MOD16 and SSEBop ET have comparable accuracy, with different performances according to climatic region [25,26]. MOD16 has been validated against several AmeriFlux (https: //ameriflux.lbl.gov/, last accessed on 29 April 2021) eddy flux tower sites, spanning different land cover types and climatic conditions, with a mean absolute error of daily ET between 0.01 and 0.66 (mm day −1 ) and root mean square error between 0.58 and 1.49 (mm day −1 ) [27].…”
Section: Introductionmentioning
confidence: 99%
“…Table 5. The simple mean of the selected three ET products and the global synthesis ET product generated by Elnashar et al [94,95], and the weighted mean results in this research (from 1982 to 2002, in mm) with corresponding bias to precipitation (in %) from 1982 to 2002 in Heihe River Basin. From Figure 16, it can be inferred that the simple mean and weighted mean of the three selected ET products generally outperformed the global synthesis ET product from 2003 to 2017.…”
Section: Discussionmentioning
confidence: 68%
“…Figure 16. Count of cells and corresponding percentages of the simple mean of the selected three ET products and the global synthesis ET product generated by Elnashar et al [94,95]. The weighted mean results in this research with level-1 and level-2 assessment and the total count of cells and their corresponding percentages are shown here.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation